Alcohol Use and Harm to Children by Parents and Other Adults. (August 2020) - Freisthler, Bridget; Wolf, Jennifer Price; Hodge, Ashleigh I.; Cao, Yiwen
This study used mixed methods to examine parent-reported harm to children (lack of supervision or physical harm) due to alcohol use by themselves or someone else as well as parent beliefs about alcohol, parenting, and harms to children. We conducted a cross-sectional general population survey of 1, 599 parents who were primary caregivers to a child aged 10 or younger and follow-up interviews with 23 parents who responded "yes" to one of the questions about alcohol use causing harm their child. Survey data were analyzed using multilevel logistic models. Compared to abstainers, parents who drank at least once a year were less likely to report that someone else's drinking caused a lack of supervision or physical harm to their child. Higher continued volumes of drinking were related to fewer reports of not watching a child closely enough. Social companionship support (having people to go out with) was related to greater odds that a parent's drinking would cause physical harm to his or her child(ren). In the qualitative analysis, four relevant themes emerged: perceived effects of alcohol use, tangible support and child supervision, immediate and distal harm, and turning points in drinking behaviors.